Structural Knockout Cascades in Metabolic Networks - Güell, Oriol (A Network-Based Approach to Cell Metabolism, 2017)
This chapter presents the analysis of the response of metabolic networks of model organisms to different forms of structural stress, including removals of individual and pairs of reactions and knockouts of single or co-expressed genes.